Pendidikan Anak Usia Dini Berbasis Ramah Anak Dalam Penerapan Pendidikan Karakter - Eka Daryati, Melia; Hatta, Muhammad (Institut Agama Islam Negeri Madura, 2024)
The aim of the research is to describe how child-friendly early childhood education is implemented in the implementation of character education at Fatma Kenanga Kindergarten, Bengkulu City. Child-friendly based early childhood education includes planning, implementation and evaluation of the implementation of character education. This study used descriptive qualitative method. Data collection techniques use observation, interviews and field notes. The data analysis technique uses the Miles Huberman model. The results of the research show that the implementation of early childhood education is child-friendly in the implementation of character education at Fatma Kenanga Kindergarten for character education planning through integrating character education values into basic competencies. The implementation of character education is implemented using several methods including the habituation method, reward method, exemplary method, consequence method, and storytelling method. Character education assessment is carried out using the observation method, conversation method, assignment method, performance method, anecdote method, and work product method